2014
DOI: 10.1103/physrevb.89.245447
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of multicontrol graphene doping using light-switching molecules

Abstract: The high carrier mobility in graphene promises its utility in electronics applications. Azobenzene is a widely studied organic molecule for switchable optoelectronic devices that can be synthesized with a wide variety of ligands and deposited on graphene. Using first-principles calculations, we investigate graphene doping by physisorbed azobenzene molecules with various electron-donating and −accepting ligands. We confirm previous experimental results that demonstrate greater pdoping of graphene for the trans … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 53 publications
2
25
0
Order By: Relevance
“…66 We further applied azobenzene molecules to modulate the interaction between the two nanoparticles and studied the interaction with graphene surfaces in the two configurations. 67,68 These studies demonstrated that one can use the configuration change to manipulate physical properties of a system. Simulations of the graphene | azobenzene | graphene vertical junction is therefore a natural extension of our long-standing interest in the added technique for gating the system.…”
Section: Graphene |Azobenzene |Graphene: Interface and Multi-controlmentioning
confidence: 99%
“…66 We further applied azobenzene molecules to modulate the interaction between the two nanoparticles and studied the interaction with graphene surfaces in the two configurations. 67,68 These studies demonstrated that one can use the configuration change to manipulate physical properties of a system. Simulations of the graphene | azobenzene | graphene vertical junction is therefore a natural extension of our long-standing interest in the added technique for gating the system.…”
Section: Graphene |Azobenzene |Graphene: Interface and Multi-controlmentioning
confidence: 99%
“…Graphene has been valued as a novel thin film semiconductor due to its special electronic properties resulting from the Dirac cone. Shifting of the Dirac cone through charge transfer has been observed in the adsoption of magnetic molecules on monolayer graphene 9,10 . Adsorption of certain adatom dimers induces spin-dependence in graphene, leading to half-metalicity in the case of iron 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption of certain adatom dimers induces spin-dependence in graphene, leading to half-metalicity in the case of iron 11 . Adding ligands to metal molecules allows for varying levels of hole doping, shifting the cone above the Fermi energy 10,[12][13][14][15] . The adsorption geometry is of note in the context of charge transfer, as seen in the adsorption of azobenzene; an external gating field induces differing charge doping between the isomers of this photoswitching molecule and graphene 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While graphene films exposed to air will show this effect, the charge carrier concentration can be increased by further chemical doping, which will reduce the resistance of the film further. 118 The doping of graphene films by substrates, 48,[125][126][127][128][129][130][131][132][133] noncovalently adsorbed molecules, 47,122,[134][135][136][137][138] or the insertion of B/N atoms into the graphene film [139][140][141][142] can either induce charge transfer from the graphene, p or hole doping, or to the graphene, electron or n, doping. Manipulation of bandgap properties is central to advancing developments in photovoltaics.…”
Section: Photovoltaic Applications and The Electronic Structure Of Grmentioning
confidence: 99%